Iterated function systems consisting of F-contractions - Secelean, Nicolae-Adrian (Fixed point theory and applications (Hindawi Publishing Corporation), 2013)
In this paper we consider a particular case of a contractive self-mapping on a complete metric space, namely the F -contraction introduced by Wardowski (Fixed Point Theory Appl. 87, 2012, doi:10.1186/1687-1812-2012-94), and provide some new properties of it. As an application, we investigate the iterated function systems (IFS) composed of F -contractions extending some fixed point results from the classical Hutchinson-Barnsley theory of IFS consisting of Banach contractions. Some illustrative examples are given. MSC: 28A80, 47H10, 54E50.